(untitled) (Fiep Bulletin - online, 2013)
Joseph Pilates developed and perfected his method throughout his life. He linked oriental techniques (flexibility, breathing and control) to western techniques (strength and resistance), creating a revolutionary method he called “Contrology “and its Center of strength was the “Power House “. All the movements are originated in this center and it encompasses the abdomen muscles, the lower part of the back and the buttocks. Considering the possibility to contribute to the development of some physical capacities, especially strength, flexibility and coordination of some youngsters who have DS, this research aims to verify the effects of Pilates classes given to these young people in the acquisition of these capacities. This is a case study of transversal cut with qualitative predominance.The sample was composed of 04 students, 02 females with chronologic age of 16 and 20 years and 02 males with chronologic age of 16 and 21 years. The tests applied were sitting and reaching (Wells bench); KTK Motor Coordination test (lateral jumps and monopedal jump);and Localized Muscular Resistance test ( abdominal). The work methodology consisted of a pretest and a posttest carried out after twenty sessions becoming evident that after the implementation of the method was an increase of strength in both legs in addition to the significant improvement in test abdominal strength, with differences between the masculine and feminine genders which may indicate a favorable opportunity for improving their quality of life of teenagers with Down syndrome, because we know the importance and necessity of physical activities at this stage.